Sustainable supply of aviation fuel in Nigeria: the status quo and the challenges - Aderibigbe Israel Adekitan (Institute of Advanced Engineering and Science, 2022)
Adequate fuel supply and availability are vital for economic sustainability. Aviation fuel accounts for more than 30% of an airline’s operating expenditure. Jet fuel price is one of the factors that determine airfare and airlines’ profitability. Nigerian airlines run on civil grade jet A-1 fuel, and almost annually, the aviation sector is plagued with jet fuel scarcity and the resulting flight delays, rescheduling, and cancellations. Jet fuel scarcity and the escalating cost are products of multifaceted factors that are related to finance, logistics, management, and policy. This study highlighted the operational specifics of the Nigerian aviation fuel sector; it identified various business opportunities that affect air transportation and discusses the main industry challenges responsible for jet fuel price volatility and scarcity in Nigeria. Instability and shortage of foreign exchange (Forex), non-refining of jet fuel locally, and absolute dependence on jet fuel importation are some of the key causal factors. A total revamp of the aviation infrastructure, a review of the current incident of multiple and exorbitant operating fees, and licensing of private and modular refineries for jet fuel production will help address jet fuel scarcity issues in Nigeria.